Corporate Governance Determinants of FII in Indian IT Firms. Issue 1 (June 2016) - Panicker, Vidya Sukumara; Mitra, Sumit; Sensarma, Rudra
Abstract: The objective of this study is to investigate the impact of corporate governance characteristics on foreign ownership in the Indian information technology industry. The ownership pattern of a firm and board characteristics are analysed to understand their impact on inflow of foreign institutional investors to the firms. Panel data for 9 years from 113 Indian IT firms, which are publicly listed, have been used. The results show that firms with more concentrated promoter holdings have lesser foreign investments. Apart from the total number of board members, measures of corporate governance including the number of independent members on board and an independent board chairman have been found to be insignificant. The outcomes point to the need of a strong performance before relying on international investments for fundraising.